VLamax correlates strongly with glycolytic Performance - Clark, B.; Macdermid, P. W. (Research Quarterly for Exercise and Sport, 2025)
VLamax estimates an athlete`s maximal glycolytic rate. This study aimed to determine the relationships between VLamax and cycle ergometry efforts with a high glycolytic energy contribution and the influence of VLamax and VO2max on the respiratory compensation point. Eleven national-to-international endurance cyclists (VO2max = 70.7 ± 5.9 ml·kg-1·min-1) completed a 15-s isokinetic test with pre- and post-lactate measurements to determine VLamax, a 1-min maximal effort, and a ramp test to exhaustion in a single test session. The main findings showed strong relationships between VLamax and the mean absolute (r = 0.83, p = .002) and relative (r = 0.88, p = .0004) power during the lactic interval of the 15-s isokinetic test. This relationship weakened when comparing VLamax with mean absolute (r = 0.52, p = .098) and relative (r = 0.29, p = .393) power during a 1-min maximal effort. Combining the VLamax and VO2max data through multiple regression resulted in a positive effect on the estimation of the respiratory compensation point. It was concluded that VLamax is a relevant indicator of maximal glycolytic rate. However, this metric currently lacks scientific validation as an accurate estimate of glycolytic rate and provides minimal extra information over using the power output from the isokinetic test alone. Practitioners may simply measure power over glycolytically demanding efforts to understand the maximal glycolytic rate of their athletes.